Identification of genes specifically methylated in Epstein–Barr virus‐associated gastric carcinomas. Issue 10 (9th August 2013) - Okada, Toshiyuki; Nakamura, Munetaka; Nishikawa, Jun; Sakai, Kouhei; Zhang, Yibo; Saito, Mari; Morishige, Akihiro; Oga, Atsunori; Sasaki, Kosuke; Suehiro, Yutaka; Hinoda, Yuji; Sakaida, Isao
<x xml:space="preserve">Abstract</x> We studied the comprehensive DNA methylation status in the naturally derived gastric adenocarcinoma cell line SNU‐719, which was infected with the Epstein–Barr virus (EBV) by methylated CpG island recovery on chip assay. To identify genes specifically methylated in EBV‐associated gastric carcinomas (EBVaGC), we focused on seven genes, TP73, BLU, FSD1, BCL7A, MARK1, SCRN1, and NKX3.1, based on the results of methylated CpG island recovery on chip assay. We confirmed DNA methylation of the genes by methylation‐specific PCR and bisulfite sequencing in SNU‐719. The expression of the genes, except for BCL7A, was upregulated by a combination of 5‐Aza‐2′‐deoxycytidine and trichostatin A treatment in SNU‐719. After the treatment, unmethylated DNA became detectable in all seven genes by methylation‐specific PCR. We verified DNA methylation of the genes in 75 primary gastric cancer tissues from 25 patients with EBVaGC and 50 EBV‐negative patients who were controls. The methylation frequencies of TP73, BLU, FSD1, BCL7A, MARK1, SCRN1, and NKX3.1 were significantly higher in EBVaGC than in EBV‐negative gastric carcinoma. We identified seven genes with promoter regions that were specifically methylated in EBVaGC. Inactivation of these genes may suppress their function as tumor suppressor genes or tumor‐associated antigens and help to develop and maintain EBVaGC.